One‐Step Synthesis of Hierarchical Structure Polydimethylsiloxane Films with Micro‐/Nanosurfaces for Application in Triboelectric Nanogenerators. Issue 12 (3rd December 2021) - Wang, Jiaxin; Wang, Kun; Qiu, Zhirong; Liu, Ye; Chen, Rong; Wu, Chaoxing; Lin, Jintang
Abstract : A one‐step, facile, scalable synthesis of a hierarchical structure PDMS film with micro/nano surface morphology is demonstrated for enhancing the triboelectric nanogenerator (TENG) performance. This fabrication method of a hierarchical structure PDMS film is simple and scalable, providing a promising solution of developing tribomaterial for practical TENG‐based electronic devices. More details can be found in article number 2100571, Chaoxing Wu, Jintang Lin, and co‐workers.